Alerts and Alarms in Conventional and ERTMS Train Driving: An Exploratory Eye-Tracking Field Study. (September 2014) - Naghiyev, Arzoo; Sharples, Sarah; Ryan, Brendan; Coplestone, Anthony; Carey, Mike
The introduction of the European Rail Traffic Management System (ERTMS) to the UK rail system has triggered a need to understand its impact on train driving. In particular it raised questions about the impact on train drivers' allocation of visual attention. This study examines impact of alerts and alarms on visual allocation of attention from an eye-tracking field study with both conventional and ERTMS drivers. The results shows that the high standard deviations for some of the results imply that there was high variance and individual differences in attention allocation strategies. This shows that not all drivers have a uniform driving style and that there may be different driving styles and variability in both types of driving, which technology needs to accommodate and training programmes need to acknowledge. The implications of the results for general understanding of visual attention allocation strategies when presented with alerts and alarms are also discussed.